Electron-rich two-, three- and four-center bonds between chalcogens: new prospects for old molecules - Gleiter, Rolf; Haberhauer, Gebhard (Coordination chemistry reviews, 2017)
The focus of this review is the nature of a third covalent bond between two divalent chalcogen centers. This bond is longer than a single bond and less than the van der Waals distance between two chalcogen atoms. Such a bond is only possible when electron density is withdrawn from the divalent chalcogens. For two sulfur centers this means S⋯S bond lengths between 2.3Å and 3.1Å. Our discussion is based on model systems, such as various trithiapentalene derivatives, 1,5-dithia-2,4,6,8-tetrazocine and related SN cage systems, the dimers of a 1,3-dithia-2,4,6-triazine radical, and systems adopting 2-center-3-electron and 4-center-6-electron bonds, respectively, between two or four sulfur centers. The leitmotiv of this review is that the loss of electron density at the divalent sulfides can lead to trivalent sulfur centers. This behavior is first rationalized qualitatively by simple MO models. The properties of the models are reproduced by high level quantum chemical methods.
Available online 3 March 2017
Gesehen am 25.07.2018